The fallacy of the closest antenna: Towards an adequate view of device location in the mobile network. (July 2022) - Ogulenko, Aleksey; Benenson, Itzhak; Toger, Marina; Östh, John; Siretskiy, Alexey
Abstract: The partition of the Mobile Phone Network (MPN) service area into the cell towers' Voronoi polygons (VP) may serve as a coordinate system for representing the location of the mobile phone devices, as demonstrated by numerous papers that exploit mobile phone data for studying human spatial mobility. In these studies, the user is assumed to be located inside the VP of the connected antenna. We investigate the credibility of this view by comparing volunteers' empirical data of two kinds: (1) VP of the connected 3G and 4G cell towers and (2) GPS tracks of these users at the time of connection. In more than 60% of connections, the user's mobile device was found outside the VP of the connected cell tower. We demonstrate that the area of a possible device's location is many times larger than the area of the cell tower's VP. To comprise 90% of the possible locations of the device connected to a specific cell tower, one has to consider the tower's VP together with the two adjacent rings of VPs. An additional, third, ring of the adjacent VPs is necessary to comprise 95% of the possible locations of the device connected to the cell tower. The revealed location uncertainty is in the nature of the MPN structure and service and entails essential overlap between the cell towers' service areas. We discuss the far-reaching consequences of this uncertainty for estimating locational privacy and urban mobility - population flows and individual trajectories. Our results undermine today's dominant opinion that an adversary, who obtains access to the database of the Call Detail Records maintained by the MPN operator, can identify a mobile device without knowing its number based on a very short sequence of time-stamped field observations of the user's connection. Highlights: Cell towers' Voronoi polygons may serve as a coordinate system for locating mobile phone devices. We compare volunteers' GPS location and the location of a cell tower that served the user's connection. Voronoi polygon of the cell tower comprises less than 40% of the users' locations. To comprise 95% of user's locations three rings of neighboring Voronoi polygons should be considered. A short sequence of field observations of the user's connection is insufficient for the user's disclosure.